Types of oral contraceptives and breast cancer survival among women enrolled in Medicaid: A competing-risk model. (January 2017) - Samson, Marsha E.; Adams, Swann Arp; Mulatya, Caroline M.; Zhang, Jiajia; Bennett, Charles L.; Hebert, James; Steck, Susan E.
Highlights: The type of oral contraceptive used had a significant difference on the rates of survival among women diagnosed with breast cancer. Progesterone-only contraceptives were associated with a significantly decreased risk of breast cancer mortality. Progesterone-only contraceptives may be a safer alternative to combined oral contraceptives among high-risk populations. Studies need to focus on women who switch from one type of oral contraceptive to another and how that may affect their health. Abstract: Introduction: Oral contraceptive pills have been implicated in the pathophysiology of breast cancer. Although many studies have examined the relationship between combined oral contraceptives (COCs) and breast cancer, there is a paucity of literature that discusses progestin-only oral contraceptives (POCs) and breast cancer. The purpose of this investigation is to examine potential associations between different types of oral contraceptives and breast cancer mortality in the South Carolina Medicaid population among different racial/ethnic groups. Methods: Subjects included 4816 women diagnosed with breast cancer between 2000 and 2013. Kaplan-Meier curves were calculated to determine time-to-mortality rates among users of oral contraceptives. Competing-risks models and Cox multivariate survival models were used to estimate the hazard ratios (HRs) and 95% confidence intervals (CIs) of breast cancer and other-cause mortality, as well as all-cause mortality. Results: POCs were associated with a significantly decreased risk of breast cancer mortality (HR: 0.07; 95% CI: 0.01, 0.52) and a non-significant increased risk of all-cause mortality (HR: 1.04; 95% CI: 0.52, 2.07). COCs increased the risk of breast cancer mortality (HR: 1.61; 95% CI: 1.14, 2.28) and all-cause mortality (HR: 1.83; 95% CI: 1.30, 2.57). Conclusion: Use of POCs may be associated with a decreased risk of breast cancer mortality. Due to the small sample size of POC users in the current study, additional research is needed to confirm these findings.